Automatic sliding gate system using tap water pressure - Ali, Mohd Basri; Abu Bakar, Mohd Hadzley; Tamin, Nor Fauzi; Zakaria, Kamarul Ariffin; Dhar Malingam, Sivakumar; Tan, Kevin Wei Chun; Ayop Azmi, Faiz Aswad (Joint Journal of Novel Carbon Resource Sciences & Green Asia Strategy, 2021)
Current automatic gates control utilizes electrically powered motor, which is relatively expensive in term of installation, operation, and maintenance that increases the cost of automatic gates. For this, a new idea with automatic gate control system that uses a source directly from tap water pressure to operate the movement of gate that is controlled with fluid power valves and cylinders is developed. Tap water is directly connected to the system and does not use any additional pump to increase the pressure. A double acting cylinder, solenoid valves and a remote-control switch are the main components in this product. The type of gate that are consider for this paper are swing gate and sliding gate. For sliding gate type, an additional device that is able to extend the maximum reach of the piston cylinder is required. It is because the length of the piston cylinder is not long enough to open the gate. After choosing the best design from some design, the selected design was further analysed and simulated using Computer Aided Design (CAD) software. Then the CAD software could determine the motion by simulation what the distance is through which the gate can move or travel. The comparison between simulation data and actual data had a percentage of error of 24.68% which refers to the movement or distance of gate travelled. Finally, both type of gate refers to swing gate and sliding gate able to work using directly tap water. In conclusion the newly developed automatic gate control for each type is cheaper in term of initial and operating cost.